Enhancing Sustainability through Green IoT: An Empirical Analysis of Energy Efficiency Realization in the Smart Cities - Istiak, Lazim; Khan, Fatin Nihal; Sakib, Tahmid; Uddin, Md. Jalal; Kabir, Ahmed Imran; Fahad, Abdullah Al (Electronic Journal of Business and Management, 2025)
This paper examines the application of Green Internet of Things technologies to maximize energy efficiency optimization in smart cities. The research is based on a survey of 126 respondents from different age group. A stratified random sample was employed for this cross-sectional study. And, investigates the interaction of the factors that ensure the success of this optimization. We applied structural equation model to analyze the response of the 126 respondents where 3 independent variables, 1 mediating variable’s impact was analyzed on the dependent variable “Smart City development” which shows impactful observations that changes according to other variables. Furthermore, the paper will focus on the different applications of energy realization in smart cities and how Green IoT has further enhanced the process. It will also look at the ways the integration of urban infrastructure and the use of renewable sources, including the policies by the government, has contributed to energy optimization. Both residents and businesses perceptions as well as those of city officials ADIES will be compared, aligned, and contrasted such that the study can highlight the critical challenges and opportunities in energy efficiency implementation in a smart city. The results will guide policymakers and other stakeholders in defining effective strategies to address Green IoT’s potential in reducing energy consumption for a possible sustainable urban life.